Assessment of the pectolinarin content and the radical scavenging-linked antiobesity activity of Cirsium setidens Nakai extracts - Lee, Young-Jun; Lee, Jin-Ha; Kim, Young-Hyun; Kim, Jae-Hwan; Yu, Seok-Yeong; Kim, Dan-Bi; Lee, Jong Seok; Cho, Myoung Lae; Cho, Ju-Hyun; Kim, Bong Kyun; Lee, Boo-Yong; Lee, Ok-Hwan (Food science and biotechnology, 2015)
Cirsium setidens Nakai contains bioactive compounds that exert biological activities. Method validation for analysis of the pectolinarin content in Cirsium setidens extracts (CSE) and radical scavenging-linked antiobesity activities using 3T3-L1 cells and C57BL/6 mice were performed. The pectolinarin content of CSE was 2.81±0.01 mg/g with a high degree of linearity in calibration curves ( R 2 =0.9999). CSE exhibited free radical-scavenging activities and a reducing power. CSE and pectolinarin inhibited lipid accumulation during adipogenesis of 3T3-L1 cells via down-regulation of adipogenic transcription factors. CSE supplementation suppressed body weight in C57BL/6 mice fed a high fat diet and reduced plasma total cholesterol, triglyceride, insulin, and glucose levels. Pectolinarin-enriched CSE can be considered as a good source of natural antioxidants and antiobesity ingredients.